Demographic Summaries for English-speaking Populations Across Quebec's RTS Territories (2011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
This document contains a series of one-page summaries highlighting the key demographic characteristics of the English-speaking populations for each of the new health territories established by the MSSS in 2015 as part of the re-organization of health services. The 25 health geographies in this series are the RTS which is the French-language acronym for the Réseau territoriale des services which correspond to the CISSS and CIUSSS territories. This series is intended as a knowledge resource for the CHSSN NPI networks.

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

2015 CHSSN-CROP Survey on Community Vitality : Findings on English-speaking Community Vitality Across Key Sectors - Pocock, Joanne (Community Health and Social Services Network, 2016)
This 2015-2016 Baseline Data Report relays key findings of the 2015 CHSSN/CROP Survey on Community Vitality as they unfold across key sectors. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income and level of bilingualism. This report from the 2015 survey is intended as a companion to the 2015-2016 Baseline Data Report entitled English Language Access to Health and Social Services in Québec, which includes a summary of results from Focus Group sessions conducted in several regions around the province.
Parallel title: Baseline Data Report 2015-2016

Baseline Data Report 2015-2016 : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
This 2015-2016 Baseline Data Report relays the health and social service findings of the 2015 CHSSN/CROP Survey on Community Vitality. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income, health status and level of bilingualism. While this report is limited to the health and social service sector, the Survey on Community Vitality (2005, 2010, and 2015) also collects the opinions, perceptions and expectations of a representative sample of English-speaking Quebecers in most regions of Quebec with respect to issues in education, human resource development, justice, culture and communications. The 2015 study replicates previous surveys conducted by CROP in 2000 for the Missisquoi Institute and again in 2005 and 2010 for the CHSSN.
Keywords: Official Language Minority Community (OLMC)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2016)
Health promotion is an activity that community organizations can adopt to enhance visibility and credibility in their communities. Health promotion activities can respond to real needs of different groups and create opportunities to engage the public system with the community organization and the constituencies it serves. For the public network, a community organization that has established a health promotion role has the potential to become a prime partner in helping an institution better serve its target population. In recent years, community networks have developed health promotion programs that have reached thousands of community members and can now demonstrate positive results. The Forum will discuss how this development is resulting in promising and best practices, and inspiring a range of public and community interests to engage in health promotion for English-speaking communities.

English-language Interpretation Services to Improve Language Access to Health and Social Services for Members of English-speaking Communities in Quebec : Status Report - Kosseim, Myléne (Community Health and Social Services Network (CHSSN), 2016)
This study aims to document the current situation regarding the use of formal interpreters as a means of language access to health and social services for English-speaking persons and to propose possible improvements to the Ministère de la Santé et des Services sociaux.
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of Richmond - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2016)
This portrait has been completed by Townshippers’ Association and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre de santé et des services sociaux Val-Saint-François and the Richmond & Region Community Learning Center. Townshippers’ Association is a non-profit, non-partisan community organization focused on promoting and supporting the interests of the English-speaking minority community in the Eastern Townships region of Quebec. The Association was founded in 1979 to ensure the English-speaking community would remain visible despite a declining population. Through a variety of initiatives, Townshippers’ works to strengthen the community and culture of English-speaking Townshippers, open doors of opportunity for youth and promote access to health, social and other services in English. Townshippers’ also strives to encourage the active participation of English-speakers in all aspects of the greater community, in order to help the English-speaking community of the Eastern Townships build bridges with their French-speaking neighbours. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Richmond and the surrounding area, in order to inform future actions.
Keywords: Official Language Minority Community (OLMC)

Poverty and Social Exclusion in Quebec's English-speaking Communities : a Brief Submitted by the Community Health and Social Services Network (CHSSN) in Contribution to the Development of the Third Action Plan to Combat Poverty and Social Exclusion by the Government of Quebec - Community Health and Social Services Network (CHSSN) (2016)
A Brief submitted by the Community Health and Social Services Network (CHSSN) in contribution to the development of the third Action Plan to combat poverty and social exclusion by the Government of Quebec.
Keywords: Official Language Minority Community (OLMC)

Key Socio-demographic Characteristics of English-speaking Children, 2011 Gaspésie – Îles-de-la-Madeleine and Census Divisions - Pocock, Joanne (2016)

Children 0 to 5 and their Parents : Québec, 2016 - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de Chaudière-Appalaches - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Abitibi-Témiscamingue - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Est-de-l'Île-de-Montréal - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Estrie – CHU de Sherbrooke - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Ouest-de-l'Île-de-Montréal - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Outaouais - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Capitale-Nationale - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Côte-Nord - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Gaspésie - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Gaspésie / Enfants de 0 à 5 ans et leurs Parents : RTS de la Gaspésie - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Mauricie-et-du-Centre-du-Québec - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Centre - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Est - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Ouest - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de Lanaudière - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de Laval - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Îles - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Laurentides - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Terres-Cries-de-la-Baie-James - Community Health and Social Services Network (CHSSN) (2016)

Community NetLink - Community Health and Social Services Network (CHSSN) (2016)
Number of pages: 8

Community NetLink - Community Health and Social Services Network (CHSSN) (2016)
Number of pages: 5

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Estrie–CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS du Centre Ouest de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS du Centre Sud de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 1 : English-speaking Men and Fathers : RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-Demographic Profiles Volume 1 : English-Speaking Men and Fathers : RTS du Saguenay–Lac-Saint-Jean - Pocock, Joanne (The Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Gaspésie - Pocock, Joanne (2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2 : English-speaking Women and Mothers : RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2 : English-speaking Women and Mothers : RTS du Saguenay – Lac-Saint-Jean - Pocock, Joanne (The Community Health and Social Services Network, 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Profil sociodémographique des enfants de 0 à 5 ans et de leurs parents RTS de l'Estrie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Le développement de la petite enfance (DPE), est une pierre angulaire du développement humain et l’enfance, est considérée comme étant la phase de développement la plus importante de la durée de la vie d’un individu. Les résultats en matière de développement à ce premier stade de la vie affectent le niveau de santé et de bien-être dont jouit une population dans son devenir. Le développement de la petite enfance est un déterminant social de la vie des communautés et il s’agit d’un processus qui est particulièrement sensible à des déterminants sociaux tels que la situation socioéconomique des familles avec des enfants de 0 à 5 ans et leur environnement social, l’accès aux services sociaux et de santé, la compétence en communication et l’alphabétisation ainsi que l’accès aux réseaux locaux de soutien social.

Regional Mini Portraits - Pocock, Joanne (2016)
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Centre-Ouest-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Centre-Sud-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Est-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Ouest-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Lanaudiére - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS du Nord-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Est-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l-Ouest-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Gaspèsie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Centre-Ouest-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Centre-Sud-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Nord-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Saguenay – Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Community Profile : Senior and Youth - Vision Gaspé-Percé Now (VGPN) (2016)
This document is a resource for community and government organizations and for those who may benefit from information on the senior and youth English-speaking populations of Gaspé. Production of this document was made possible by the financial support of Health Canada and the demographic data has been provided by the Community Health and Social Services Network (CHSSN).